Myo-Inositol 1,3-acetals as early intermediates during the synthesis of cyclitol derivatives - Gurale, Bharat P.; Sardessai, Richa S.; Shashidhar, Mysore S. (Carbohydrate Research, 2014)
Synthetic sequences starting from commercially available myo-inositol necessarily involve protection-deprotection strategies of its six hydroxyl groups. Several strategies have been developed/attempted over the last several decades leading to the synthesis of naturally occurring phosphoinositols, their analogs, and cyclitol derivatives. Of late, myo-inositol 1,3-acetals, which can be obtained by the reductive cleavage of myo-inositol orthoesters have emerged as early intermediates for the synthesis of phosphorylated and other inositol derivatives. This mini-review is an attempt to illustrate the economy and convenience of using myo-inositol 1,3-acetals as early intermediates during syntheses from myo-inositol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acetal; Cyclitol; Inositol; Protecting group; Signal transduction